Investigating the Demographics and Mobile Phone Technology Used by University Students in Nairobi, Kenya - Wasiaya, Onyango Christopher; Serede, Sikolia Geoffrey; Kinoti, Mberia Hellen (Innovations in Science and Technology Vol. 3, 2022)
Purpose: The moderating effect of demographic factors on mobile phone technology use by undergraduate public university students in Nairobi, Kenya was investigated in this study. The study's goal was to determine the moderating effect of demographic characteristics on undergraduate university students' use of mobile phone technology. Methodology: As a theoretical framework, the research employed the media technological determinism theory. The target population consisted of 246,871 undergraduate university students from Nairobi's six public universities. The quantitative research design was used. As data collection tools, self-administered questionnaires were used. Purposive sampling was used in this study to generate a sample size of 573 undergraduate students. Descriptive statistics were used to analyse the data, which was then processed using the Statistical Package for Social Sciences (SPSS) version 22. Findings: The findings revealed that undergraduate university students' use of mobile phone technology was not influenced by demographic factors. The study concluded that respondents' demographics had no moderating effect on the relationship between undergraduate public university students and mobile phone technology use levels. Unique Contribution to Theory and Practice and Policy: Since this research focused on undergraduate university students in public universities in Nairobi, Kenya, the researcher recommends that another research could be carried among post graduate students and also among private universities to find out if demographic factors may be affecting mobile phone technology use.